The Vaginal Microbiome of Transgender Men. (1st January 2019) - Winston McPherson, Gabrielle; Long, Thomas; Salipante, Stephen J; Rongitsch, Jessica A; Hoffman, Noah G; Stephens, Karen; Penewit, Kelsi; Greene, Dina N
Abstract: BACKGROUND: Hormonal changes influence the composition of vaginal flora, which is directly related to the health of an individual. Transgender men prescribed testosterone experience a vaginal hormone composition that differs from cisgender women. To the author's knowledge, there are no clinical studies evaluating the influence that testosterone administration has on the vaginal microbiome. METHODS: Vaginal swabs were self-collected by a cohort of self-identified healthy transgender men prescribed testosterone for at least 1 year (n = 28) and from cisgender women who were used as the comparator (n = 8). Participants completed a questionnaire to indicate the mode and dose of testosterone administration, sexual history, and vaginal health. Serum was collected for hormone analysis. Bacterial community profiles were assessed with broad-range PCR primers targeting the V3–V4 hypervariable region of the 16S bacterial rRNA, next-generation sequencing, and analysis by phylogenetic placement. RESULTS: Compared to cisgender women, the vaginal floras of transgender men were less likely to have Lactobacillus as their primary genus. Intravaginal estrogen administration was positively associated with the presence of Lactobacillus in transgender men ( P = 0.045). Transgender men had a significantly increased relative abundance of >30 species and a significantly higher α diversity ( P = 0.0003). The presence of Lactobacillus was significantly associated with a lower α diversity index ( P = 0.017). CONCLUSIONS: The vaginal microbiome of transgender men who were assigned a female sex at birth and use testosterone may differ from that of cisgender women. Intravaginal estrogen administration may reduce these differences by promoting colonization with Lactobacillus species and decreasing α diversity.